The impact of AI and Python on Accounting Audit in North American enterprise systems for the years 2021 to 2023 - Barrera Beraun, Stephe; Enciso Tomasto, Alexandra; Leon Olivares, Mario; Llamoca Álvarez, Nidia; Larios, Omar; Mendoza Ibarra, Veronica; Urdanegui Sibina, Rosella (LACCEI, 2025)
In the rapidly evolving domain of accounting auditing, the integration of Artificial Intelligence (AI) and Python has emerged as a transformative element in North America between 2021 and 2023. This study examines the impact of these technologies on internal control assessment, advanced data analysis, and fraud and anomaly detection. These tools have enhanced audit processes by automating repetitive tasks, enhancing the accuracy of analysis of large volumes of data, and facilitating early identification of risks. The study underscores the significance of advanced algorithms that enable a proactive approach to risk management, while concurrently highlighting the ethical and security challenges posed by the utilization of these technologies. It emphasizes the necessity for governance policies and continuous training to ensure the effective and ethical use of AI and Python in auditing processes. The study's findings underscore the importance of human oversight and ethical regulation to ensure the effectiveness and transparency of these technologies.